STRENGTHENING EARLY READING SKILLS THROUGH A PHONICS-BASED APPROACH IN ENGLISH LESSONS - Tiarnita Maria Sarjani; Nemia Exdima Hutagaol; Agnes Paska Dewita Saragih; Cerin Angelyva Br Banjarnahor; Sindy Sindy (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2026)
Strengthening early reading abilities is an important foundation for supporting students’ literacy growth, particularly in the lower grades of elementary school. This study investigates the effectiveness of using a phonics-based approach to improve students’ initial English reading skills. A descriptive qualitative design was employed, with data gathered through classroom observations, reading assessments, and interviews with teachers. The results reveal that phonics instruction, which includes letter-sound recognition, blending, segmenting, and decoding activities, significantly enhanced students’ ability to read simple English vocabulary and identify phonemes correctly. Students also showed increased engagement and confidence during reading sessions. These findings indicate that phonics provides a systematic and effective model for early English literacy instruction in primary classrooms. The study recommends that English teachers apply structured phonics strategies to strengthen reading readiness and literacy achievement.